The Postmodern Challenge of Historiography in Contemporary Canadian Fiction: : Kate Pullinger’s Weird Sister and the Silent Voices in History - Fonfárová, Vladimíra (American & British Studies Annual, 2022)
As defined by Georg G. Iggers and promoted by Hayden White, the postmodern challenge of historiography calls into question the objective enquiry and truth value of history writing. Many works of fiction have embodied this trend, embracing the challenge by exploring objectivity and the retrievability of the past. In contemporary Canadian literature, such cases are also to be found. The novel Weird Sister (1999) by Kate Pullinger thematizes history and history writing, utilizes Gothic elements, and employs the elements of historiographic metafiction, e.g. as characterized by Linda Hutcheon. The book features characters representing the so‐called silent voices whose testimony had remained lost in the official historical record. This paper aims to show that the depiction of the impossibility of uncovering the truth about the past represents a significant contribution by contemporary fiction authors to the postmodern challenge of historiography, with Pullinger’s novel emerging as a notable contribution to this discourse.